Exploration of The Causes of Bullying in the Alpha Generation: "Bumi Nyiur Melambai" - Rani Darojah; Raden Sudarwo; Urip Tri Wijayanti; Sri Sugiharti; Faoyan Agus Furyanto (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Bullying occurs frequently in educational and school environments, workplaces, homes, and playgrounds. North Sulawesi Province has a higher bullying rate than the national average, at 27.83 percent versus 26.80 percent. Bullying occurs more frequently among Grade 5 elementary school students than in middle and high school. The study seeks to identify the factors that contribute to bullying among the alpha generation in Manado, North Sulawesi Province. The qualitative research technique focuses on two elementary schools in Manado: Advent Tikala Elementary School for private elementary schools and SDN 06 state elementary schools. Data collection began with focus group discussions with children and their parents, followed by interviews with stakeholders such as teachers, school principals, childcare NGOs, universities, regional government (province, Manado city), and the media. Observations on behaviours that lead to bullying. Data about bullying in school has been documented. The data were analysed descriptively. Research on the variables that produce bullying, beginning with the family, has revealed parenting patterns, a lack of parental attention, verbal and nonverbal pressure, and kid copying. Both peers and children choose the wrong friends, engage in harmful behaviour, and establish gangs. Third, media (inappropriate use of gadgets, premature introduction of gadgets, and lack of parental control). The fourth culture involves calling their parents' names. The five schools have not implemented character education optimally, and educators have not improved their bullying prevention practices. The six internal/character characteristics are as follows: children with temperamental, envious, jealous, and spiteful personalities are more likely to be perpetrators, while quiet youngsters dislike socializing, and less bright children are the victims. Recommendations necessitate efforts with parents.